The Parameters Change with Different Operation Conditions of Solar Chimney Power Plant Model - Hannun, Rafid M.; E.Najim, Salih; Khalaf, Mohammed H. (Basrah Journal for Engineering Sciences, 2014)
The solar chimney power plant is one of the modern models studied on the world. This study presents an engineering and numerical analysis of solar chimney with different parameters. Also, it studies the comparison of two collector base shapes(circular and hexagonal) depend on the five storage material types and their effects on the heat transfer, velocity, efficiency, etc. inside the solar chimney system by considering the solar array intensity equations and the energy equation to calculate the heat transferred and stored by applying the laws of CFD. The finite volume method is used to analyze the geometry physical model by applying a commercial Fluent 6.3 code with Gambit 2.3. The obtained results show that the efficiency of solar chimney is increased by increasing the area of solar glassed collector with circular base shape than the others of polygonal or rectangular one because the circular was covered large area of system. So, the circular ground collector shape for thermal storage is the favour because it is the better to increase the velocity of entering air and to increase the efficiency of turbine. In addition to that the black Pebble storage plate is the better material for heat storage which is convected to air passed for operation of turbine than the other types aluminum, tar, copper and steel seriously.